Plant growth regulators increase productivity of 'Packham's Triumph' pear in southern Brazil - Brighenti A.F.* (2011)
Poor fructification is one of the biggest problems with the production of pears in Brazil. The absence of fertilization in pear flowers results in lower fruit set and reduction in orchard productivity. When pollination is insufficient, it is necessary to use bioregulators. The objective of the present study was to evaluate the effect of different plant growth regulators in increasing productivity of 'Packham's Triumph' pears. The experiment was conducted in São Joaquim city (28amp;°17'S; 49amp;°56'W, altitude 1350 m), Santa Catarina State, Brazil. The experiment was conducted in a randomized block design. The treatments were: 1 - Promalin® (1 ml L-1) at full bloom; 2 - Promalin® (0.3 ml L -1) applied at the beginning, full and end of bloom; 3 - Prohexadione-Ca (0.65 g L-1) at full bloom; 4 - Prohexadione-Ca (1.25 g L-1) at full bloom; 5 - Prohexadione-Ca (2.5 g L-1); 6 - ReTain® (2 g L-1) 15 days after full bloom (DAFB); 7 - Promalin® (1 ml L-1) at full bloom+ReTain ® (2 g L-1) 15 DAFB; 8 - Promalin® (1 ml L-1)+ReTain® (2 g L-1) at full bloom; 9 - Promalin® (1 ml L-1)+Prohexadione-Ca (0.65 g L -1) at full bloom; 10 - Control (water). Productivity (ton ha -1), fruit diameter, weight, deformation, seed number, flesh firmness, total soluble solids, acidity and pH were evaluated. Treatment 7 did not differ from 8 in fruit productivity and diameter and both were better than the others. The control presented the highest number of seeds and treatment 8 the highest rate of fruit deformation. The other variables did not differ among treatments.